Biomass production and heavy metal absorption by four plants grown at the moravia dump, medellin, colombia (2010)
Dumps are sites where the presence of high heavy metal (HM) concentration is a common occurrence, creating the need for implementing restoration processes immediately after their closure. In the 7.6 ha and 45 m high Morro de Moravia dump, arose from the disposal of Medellín solid wastes from 1974 to 1984, previous studies have demonstrated high contents of contaminants, including HM, prompting the need to identify effective mechanisms to implement its restoration. The objective of this study was to evaluate the adaptation, growth and phytoremediation capacity of Bidens pilosa, Lepidium virginicum, Brachiaria decumbens and Arachis pintoi. Content of HM (mg/kg) in Moravia residue matrix went from 17 to 8193 for Pb, 44 to 564 for Cr, 0.2 to 339 for Cd and 77 to 1679 for Ni. Measurements of plant cover, plant height and dry matter production at all plant species studied suggested adequate growth and adaptation to the Moravia dump conditions. Plant absorption of HM showed the pattern Cr and gt; Cd and gt; Ni and gt; Pb. Estimated bioconcentration factors were generally low, and maximum values were 0.36 in A. pintoi (Cr), 2.96 in B. pilosa (Cd) and 0.26 in B. decumbens (Ni). However, our estimations of the phytoremediation potential of the assayed species, suggested they possess low remediation efficiency. Further investigation should be carried out in order to identify more efficient HM accumulators, and to test the use of technologies such as modification of pH, rhizoremediation or the use of genetically enhanced accumulators to increase HM availability to plants